Weather Information for Garden City, 2023 - Anthony Zukoff (Kansas Agricultural Experiment Station Research Reports, 2024)
Summary of 2023 weather for research conducted at the research locations included in the 2024 Western Kansas Agricultural Research report.
Keywords: Weather; precipitation; Garden City; Kansas; temperature; wind; evaporation